Effectiveness and cost-effectiveness of height-screening programmes during the primary school years: a systematic review. Issue 4 (2nd May 2007) - Fayter, D; Nixon, J; Hartley, S; Rithalia, A; Butler, G; Rudolf, M; Glasziou, P; Bland, M; Stirk, L; Westwood, M
Abstract : Objective: To determine the effectiveness and cost-effectiveness of height screening (of children aged 4 to 11) to identify height-related conditions. Design: Systematic review and economic modelling. Setting and intervention: We included published and unpublished screening studies of any design, except case reports, conducted in any setting that measured children's height as part of a population-level assessment. Studies were identified by electronic database searches, contact with experts and from bibliographies of retrieved studies. Participants: Children aged between 4 and 11 years. Outcome measures: Diagnostic yield of height-related conditions and change in quality of life, as measured by quality-adjusted life years (QALYs), for early versus late treatment of underlying conditions. Results: Twelve studies described a height-screening programme and provided data on the diagnostic yield of newly diagnosed height-related conditions. Where reported, yield for growth-hormone deficiency (per 1000 children screened) ranged from 0.05 (1 in 20 000) to 0.62 (approximately 1 in 1500) and for Turner syndrome (per 1000 children screened) was between 0.02 (1 in 50 000) and 0.07 (approximately 1 in 14 000). As a secondary gain, children with other potentially treatable conditions were identified; diagnostic yields ranged from 0.22 to 1.84 per 1000 children screened. Three studies did not detect any new cases, but all of these studies had methodological limitations. Economic modelling suggested that height screening is associated with health improvements and is cost effective for a willingness to pay threshold of £30 000 per QALY. Conclusions: This review indicates the utility and acceptable cost-effectiveness of height screening arising from increased detection of height-related disorders and secondary pick-up of other undiagnosed conditions. Further research is needed to obtain more reliable data on quality of life gains and costs associated with early interventions for height-related conditions. The exact role of height-screening programmes in improving child health remains to be determined.